Working classification of chronic myeloproliferative disorders based on histological, haematological, and clinical findings. Issue 3 (March 1986) - Burkhardt, R; Bartl, R; Jäger, K; Frisch, B; Kettner, G; Mahl, G; Sund, M
Abstract : Bone marrow biopsies of 850 patients with chronic myeloproliferative disorders were taken at initial diagnosis; and 169 sequential biopsies over periods of one to 188 months. Three micron sections of all biopsies were evaluated semiquantitatively with reference to the proliferating cell lines, anomalies of megakaryocytes, and fibrosis or osteosclerosis. Correlations between initial histological findings, clinical, haematological, and survival data were analysed statistically. The predominant cell lines distinguished the classical entities of polycythaemia vera, primary thrombocythaemia, and chronic myeloid leukaemia and correlated with their different prognoses, while megakaryocytes characterised subgroups that were prone to fibrotic or blastic transformation. Based on the initial histological, clinical, and haematological data analysed a working classification of chronic myeloproliferative disorders was proposed that permits recognition of both typical and atypical cases of chronic myeloproliferative disorders.